Penguatan Kemandirian Pangan Rumah Tangga Melalui Hidroponik Vertikal Dan Pemasaran Digital Berbasis E-Commerce - Fitri Ayu; Benriwati Maharmi; Desi Yasri; Jesaja Ginting; Ermawati; Jean Riko Kurniawan Putra; Nurhasnah (STMIK Royal, 2026)
Abstract: Urban household food security is still constrained by limited land availability and a high dependence on external supply. A community service program conducted in Berkah Family Village Housing, Kubang Jaya Village, aims to enhance food self-sufficiency through vertical hydroponics, organic waste processing, and e-commerce–based digital marketing training. Using a Participatory Action Research (PAR) approach, the program increased hydroponic knowledge from 30% to 85%, assembly skills from 15% to 80%, plant maintenance understanding from 25% to 78%, and e-commerce skills from 0% to 75%. A single hydroponic tower produces 7.2–14 kg per cycle, with potential income ranging from IDR 435,000 (pakcoy) to IDR 1,400,000 (lettuce). Kale can be harvested continuously for more than one year every 7–10 days, yielding an average of 105 grams per plant and generating up to IDR 1,100,000 per harvest. Additionally, 20 households are able to process kitchen waste into liquid fertilizer. Overall, the program has proven effective in strengthening household food security and economic resilience while supporting the achievement of the SDGs. Keywords: community empowerment; family food security; organic waste processing; urban farming; vertical hydroponics Abstrak: Ketahanan pangan keluarga di perkotaan masih terkendala keterbatasan lahan dan tingginya ketergantungan pada pasokan luar. Program pengabdian di Perumahan Berkah Family Village, Desa Kubang Jaya, bertujuan meningkatkan kemandirian pangan melalui hidroponik vertikal, pengolahan limbah organik, dan pelatihan pemasaran digital berbasis e-commerce. Dengan pendekatan Participatory Action Research (PAR), terjadi peningkatan pengetahuan hidroponik dari 30% menjadi 85%, keterampilan perakitan dari 15% menjadi 80%, pemahaman perawatan tanaman dari 25% menjadi 78%, serta kemampuan e-commerce dari 0% menjadi 75%. Satu unit tower hidroponik menghasilkan 7,2–14 kg per siklus dengan potensi pendapatan Rp. 435.000 (pakcoy) hingga Rp. 1.400.000 (selada). Tanaman kale dapat dipanen berkelanjutan sampai lebih satu tahun, tiap 7–10 hari dengan rata-rata 105 gram per tanaman dan potensi Rp.1.100.000 per panen. Sebanyak 20 keluarga juga mampu mengolah limbah dapur menjadi pupuk cair, sehingga program ini efektif memperkuat ketahanan pangan dan ekonomi rumah tangga serta mendukung SDGs. Kata kunci: pemberdayaan masyarakat; ketahanan pangan keluarga; pengolahan limbah organik; pertanian perkotaan; hidroponik vertikal